FRACTURE RESISTANCE AND FAILURE PATTERN OF TEETH SUBMITTED TO INTERNAL BLEACHING WITH 37% CARBAMIDE PEROXIDE, WITH APPLICATION OF DIFFERENT RESTORATIVE PROCEDURES - Bonfante, Gerson (J Appl Oral Sci, 2006)
OBJECTIVE. This study investigated the compressive fracture strength and failure pattern in premolars submitted to endodontic treatment and internal bleaching with 37% carbamide peroxide for 21 days, with application of different restorative procedures. MATERIAL AND METHODS. Six groups were employed (n = 10): 1) non-bleached teeth and pulp chamber sealed with IRM; 2) bleached teeth and pulp chamber sealed with IRM; 3) bleached teeth and pulp chamber filled with light cured composite resin; 4) bleached teeth, root canals prepared at 10mm, filling of the root canal and pulp chamber with IRM; 5) bleached teeth, root canals prepared at 10mm, luting of prefabricated metallic post with zinc phosphate and pulp chamber sealed with composite resin; 6) bleached teeth, root canals prepared at 10mm, luting of glass fiber post with resin cement and pulp chamber sealed with composite resin. After 24-hour storage in distilled water, the specimens were submitted to compressive fracture strength testing in a universal testing machine. RESULTS. The following values were found: Group 1 – 56.23kgf; Group 2 – 48.96kgf; Group 3 – 53.99kgf; Group 4 – 45.72kgf; Group 5 – 54.22kgf; Group 6 – 60.12kgf. The analysis of variance did not reveal statistically significant difference between groups (p<0.05), suggesting that internal bleaching with 37% carbamide peroxide did not weaken the dental tissues. The largest number of unfavorable fractures was observed for Groups 2 (50%), 4 (40%), and 5 (30%). Group 6 exhibited the most favorable failure pattern. CONCLUSIONS. The results suggest that internal bleaching with 37% carbamide peroxide did not significantly weaken the teeth. Among the bleached teeth, those with temporary IRM restorations or metallic posts demonstrated the most unfavorable fracture pattern, whereas the most favorable fracture pattern occurred in teeth restored with composite resin and glass fiber posts.